Disciplining terror how experts invented "terrorism" - Stampnitzky, Lisa (Cambridge University Press, 2013)
Since 9/11 we have been told that terrorists are pathological evildoers, beyond our comprehension. Before the 1970s, however, hijackings, assassinations, and other acts we now call 'terrorism' were considered the work of rational strategic actors. 'Disciplining Terror' examines how political violence became 'terrorism,' and how this transformation ultimately led to the current 'war on terror.'This book investigates how the concept of terrorism has been developed and used over recent decades.